Pneumococcal meningitis with vertebral osteomyelitis, iliopsoas abscess, and infected abdominal aortic aneurysm. Issue 1 (13th December 2017) - Mitsutake, Akihiko; Matsumoto, Hideyuki; Hatano, Keiko; Matsuura, Sohei; Takayama, Toshio; Yamamoto, Kota; Hoshina, Katsuyuki; Ikemura, Masako; Hashida, Hideji
Abstract: A 69‐year‐old man with a past history of asymptomatic abdominal aortic aneurysm developed pneumococcal meningitis. Antibiotic therapy improved his meningitis. However, he also developed vertebral osteomyelitis, iliopsoas abscess, and infected abdominal aortic aneurysm. The aneurysm was sequentially dilated, suggesting the impending rupture. An emergency open aneurysm repair using a tube homograft was performed. All of the vertebral osteomyelitis, iliopsoas abscess, and infected abdominal aortic aneurysm are rare complications. In particular, if a patient with bacterial meningitis has a preexisting aortic aneurysm, infected aortic aneurysm should be noted. To prevent the rupture of the aneurysm, the emergent vascular surgery including aorto‐aortic homograft substitution should be considered.